Problems and Solutions in Thermoelasticity and Magneto-thermoelasticity - Das, B. (Springer International Publishing : Imprint: Springer, 2017)
This book presents problems and solutions of the mathematical theories of thermoelasticity and magnetothermoelasticity. The classical, coupled and generalized theories are solved using the eigenvalue methodology. Different methods of numerical inversion of the Laplace transform are presented and their direct applications are illustrated. The book is very useful to those interested in continuum mechanics.